New approach to assess and rank the impact of revolute joint wear on the kinematic accuracy in the low-velocity planar mechanism. (December 2016) - Lai, Xiongming; Lai, Qingfang; Huang, He; Wang, Cheng; Yang, Jianhong; Zhang, Yong
Highlights: The calculation of revolute joint wear in low-velocity mechanisms is proposed. "Position factor" and "wear factor" are proposed to assess joint wear's impact. The first and second sensitivity indices are proposed to assess and rank the impact of joint wear. The joints that affect the kinematic accuracy most can be identified as the weakness due to their wear. Abstract: During the movement of the low-velocity planar mechanisms, the joint wear belonging to different positions have fairly distinctive impact on kinematic accuracy. Currently, there is a shortage of relevant approaches, functioned as a guidance to identify their major and minor effects on kinematic accuracy, which is adverse to confirm the weakest joint and restrain its impact. Aiming at this problem, based on the model of joint clearance, an approach to the calculation of its wear is proposed, and an analytical method of the sensitivity of kinematic accuracy to the joint wear is further suggested. The sensitivity method is applicable to practical engineering problems since the impact of both "position factor" and "wear factor" of the revolute joint wear on kinematic accuracy are considered. Through comparison and contrast of sensitivity, the impact on the kinematic accuracy by the joint wear can be assessed and ranked so that the weakest joint will be identified afterwards. Finally, the proposed method is verified via illustrative examples.